Does every goose count? Pitfalls of surveying breeding geese in urban areas - Kowallik, Christine; Koffijberg, Kees (Wildfowl, 2013)
The size of local breeding populations of Greylag Geese Anser anser and Canada Geese Branta canadensis at a suburban site in Northrhine-Westphalia, Germany, was assessed between 2010 and 2012 using four different methods: nest surveys, counts of territorial pairs and two types of brood counts. For both species, nest surveys generated the highest estimate of breeding numbers. Geese recorded as territorial pairs made up 50–75% of the apparent nesting pairs (73% of all nesting Greylag Geese and 60% of all nesting Canada Geese in an area surveyed extensively in 2011). Numbers of broods recorded never exceeded 50% of the number of apparent nesting pairs. Moreover, the number of broods observed was heavily dependent on fieldwork intensity, with most broods found during highly frequent (twice-weekly) counts that allowed effective monitoring of the fate of individual broods, even without using individual marking. When broods are monitored less frequently, one has to rely on the maximum number of broods observed simultaneously in determining the number of pairs with young, which in our study represented only 10–25% of the apparent nesting number. Although nest counts may provide the highest estimate of breeding goose abundance, they may be impractical or undesirable (e.g. because of disturbance to other breeding birds). In such cases, territorial pair assessments may be the preferred method, if separation of breeding and non-breeding birds is not made too conservatively. For instance, only those birds that obviously behave as non-breeders, by leaving the nesting areas to feed on nearby agricultural fields during daytime, should be excluded from breeding numbers. Although counts of the total number of broods can contribute to measures of reproductive success, they can considerably underestimate the number of goose breeding pairs.